The involvement of Muslim-owned small medium enterprises (SMEs) in e-commerce: the role of technological infrastructure and digital literacy during pandemic of Covid-19 in Perlis, Malaysia / Mohd. Zaki Shahabuddin ... [et al.] - Shahabuddin, Mohd. Zaki; Mohd Jamil, Rozana; Mat Bistaman, Izwan Nurli; Muhamad, Fatimah Noni; Subri, Nor Izham (Universiti Teknologi MARA, Perlis, 2022)
The global outbreak of pandemic Covid-19 has shown an increase in E-business, particularly in E-commerce. As more people opt for E-commerce and online purchasing, SMEs must diversify their revenue and profitability by transitioning to online operations to sustain during the pandemic. Therefore, this study aims to obtain information, then descriptively analyse the technological infrastructure and digital literacy with respect to the involvement in E-commerce by Muslim entrepreneurs. This study used a questionnaire as the instrument of the research. It was done in the state of Perlis, Malaysia with Muslim entrepreneurs involved in SMEs was chosen using a convenient sampling technique. A total of 50 questionnaires were returned satisfactorily. Data were analysed and interpreted by using Statistical Package for Social Science (SPSS) computer software program. A descriptive study that includes mean, standard deviation and percentages for each component in technological infrastructure and digital literacy were employed. Most of the respondents have an uncertain view of technological infrastructure but agreed